2011
DOI: 10.1523/jneurosci.6215-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Activation Suppresses Microtubule Growth and Spine Entry

Abstract: Dynamic microtubules are important to maintain neuronal morphology and function, but whether neuronal activity affects the organization of dynamic microtubules is unknown. Here, we show that a protocol to induce NMDA-dependent long-term depression (LTD) rapidly attenuates microtubule dynamics in primary rat hippocampal neurons, removing the microtubule-binding protein EB3 from the growing microtubule plus-ends in dendrites. This effect requires the entry of calcium and is mediated by activation of NR2B-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 93 publications
2
106
0
1
Order By: Relevance
“…Because immunofluorescence analysis did not detect MT signals in spines, it has been believed that actin filaments and their regulatory proteins play a central role in spine morphogenesis (Kaech et al, 2001). However, recent studies have revealed that MTs stochastically invade into spines in an activity dependent fashion (Kapitein et al, 2011;Gu et al, 2008;Hu et al, 2008). These studies also demonstrated that MT dynamics are essential for maintaining the shape of mature dendritic spines by regulating the dendritic localization of p140Cap, which is required for actin reorganization in spines ( Fig.…”
Section: Par-1 Plays Essential Roles In Maintaining Dendritic Spine Mmentioning
confidence: 98%
“…Because immunofluorescence analysis did not detect MT signals in spines, it has been believed that actin filaments and their regulatory proteins play a central role in spine morphogenesis (Kaech et al, 2001). However, recent studies have revealed that MTs stochastically invade into spines in an activity dependent fashion (Kapitein et al, 2011;Gu et al, 2008;Hu et al, 2008). These studies also demonstrated that MT dynamics are essential for maintaining the shape of mature dendritic spines by regulating the dendritic localization of p140Cap, which is required for actin reorganization in spines ( Fig.…”
Section: Par-1 Plays Essential Roles In Maintaining Dendritic Spine Mmentioning
confidence: 98%
“…The frequency of invasion is low, with approximately 1% of dendritic protrusions containing a microtubule at any one time (Hu et al 2008) and the dwell time is in the order of minutes but, importantly, dwell time and the frequency of invasion are enhanced by pharmacological interventions that mimic LTP (Gu et al 2008, Hu et al 2008Mitsuyama et al 2008;Jaworski et al 2009;Merriam et al 2011) and supressed by eliciting LTD (Kapitein et al 2011). Depolymerisation of microtubules in dendrites using drugs such as nocodazole reduces spine density along the dendrite without affecting dendrite numbers (Jaworski et al, 2009).…”
Section: Activity-driven Microtubule Capture and Insertion Into Dendrmentioning
confidence: 99%
“…Notably, these studies show that classical MAPs act as direct regulators of the actions of EBs in neuronal cells, pointing to the existence of a functional interplay between these two types of microtubular proteins. 10,11 Typical localization of classical MAPs and EBs on MTs differ: while EBs accumulate at MT plus-ends in a comet-like pattern, classical MAPs bind along MTs. 7,9 How can then EBs be directly regulated by MAPs?…”
Section: Maps As Modulators Of Ebs Actions In Neuronsmentioning
confidence: 99%